A reconnaissance botanical survey of the Lower Orange River (Blouputs to Onseepkans) in the Northern Cape, South Africa - H. Bezuidenhout; Christine L. Jardine (Koedoe: African Protected Area Conservation and Science, 2001)
In the past, the alluvial floodplains of the Orange River were covered with riverine shrubland and woodland. However, there are indications that this has changed and that this vegetation and habitat has been influenced by a number of factors, namely: expansion of irrigated crop farming; grazing pressure; and upstream dam construction. A botanical assessment was carried out along the Orange River between Blouputs and Onseepkans, in the Northern Cape to determine the nature and extent of the changes to the riverine vegetation, as well as to investigate the distribution of Combretum erythrophyllum and Rhus lancea. Only two specimens of Combretum erythrophyllum were noted whereas no Rhus lancea specimens were noted. There are indications that both the expansion of irrigated crop farming and grazing pressure has affected the vegetation of the plain and riverine area along the Orange River. Downstream from the farm Raap-en-Skraap (2819DA Skuitdrif), the natural vegetation of the riverbanks and islands is being replaced by alien plant species.